The effect of Laurus nobilis on the blood and lenses antioxidant activity in rabbit under fat-enriched diet - Casamassima, D; Chiosi, F; Vizzarri, F; Palazzo, M; Costagliola, C (Physiological research, 2017)
Fat-enriched diet is strongly associated with cataract development. Laurus nobilis shows antioxidant activity. Herein we evaluated the effect of Laurus nobilis oral administration on the blood and lenses antioxidant activity in rabbits under fat-enriched diet. Sixty rabbits divided into 4 groups were used. One group represented the control (N-CTR). The second group (P-CTR) fed a diet supplemented with 2.5 % of pig fat; the third group (EXP1) received a diet supplemented with 2.5 % of pig fat and 1 g/kg of dried-bay leaves; the fourth group (EXP2) was treated with dried-bay leaves at the rate of 1 g/kg of feed. At baseline and at the end of the study (56 days) the following blood parameters were determined: thiobarbituric acid reactive substances (TBARS), reactive oxygen metabolites (ROMs), total phenols, superoxide dismutase (SOD), oxygen radical absorbance capacity (ORAC(pca)), ferric ion reducing antioxidant power (FRAP), retinol and alfa-tocopherol. At the end of the follow-up, the eyes were enucleated and the antioxidant profile, such as total antioxidant activity (TAC), TBARS, retinol and alfa-tocopherol of lenses was evaluated. Plasma ROMs and TBARS levels were statistically lower in the groups receiving bay leaves integration. A significant increase of plasma retinol, FRAP and ORAC(pca) levels was found in EXP1 and EXP2 groups, whereas plasma alfa-tocopherol resulted statistically higher only in EXP2 group. Bay leaves supplementation enhanced TAC, retinol and alfa-tocopherol in rabbit lens, particularly in EXP2 group; whereas lenses TBARS levels significantly decreased in both treated groups. These findings demonstrate that Laurus nobilis oral administration exerts a protective effect on the risk of cataract development in rabbits under fat-enriched diet.
Keywords: oční čočka; Animals; Rabbits; vztah mezi dávkou a účinkem léčiva; Antioxidants; vavřín; dietní tuky; Dietary Supplements; Diet, High-Fat; Lens, Crystalline; potravní doplňky; Laurus; Dose-Response Relationship, Drug; fytoterapie; Male; antioxidancia; králíci; zvířata; mužské pohlaví; dieta s vysokým obsahem tuků; Dietary Fats; Phytotherapy